Shifting Activities in Warung kopi as Third Places in Pontianak City - Dwi Millenia Ariyani; Jimly Al Faraby (Syntax Literate, 2026)
Background: Warung kopi are often seen as a representation of informal public space, serving as a third place that plays an important role in the lives of people in Pontianak City and has become part of the city’s cultural identity. However, urban social dynamics and technological developments have shifted the role of coffee shops as a third place. Objective: This study aims to identify the characteristics of warung kopi in Pontianak City as places for social activities in accordance with the third-place theory (Oldenburg, 1989) and to examine shifts in activities currently occurring in warung kopi. Methods: This study uses a descriptive qualitative approach through semi-structured interviews with customers, owners, and workers at 51 warung kopi spread across Pontianak City. Results: The results of the study indicate that, currently, social activities are no longer the main activity in Warung kopi; other activities blur the role of Warung Conclusion: Kopi as social spaces and turn them into spaces to meet the needs of community life.